Rhetoric in Islamic Tradition: Paradigm and Its Development - Umdatul Hasanah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
Rhetoric has an essential role in developing Islamic civilization and da’wah. Rhetoric in the Islamic tradition has a dualistic paradigm that appears with two faces, specifically balaghah and khithobah. The character of balaghah is inherent in the rhetorical tradition, where the qualification of the message language is essential, including eloquence, meaning, and metaphor. In comparison, the khithobah character is attached to the quality aspects of the message content and the technique of delivering the message. This literature research found that the two faces of this rhetoric have further developments, one is progressive, and the other is still stagnant. The progress of balaghah is not only based on the role of Arabic as the Quran language but also the miracle of the Quran language itself. While khithobah is an essential part of delivering Islamic symbols, it is still considered a mere praxis and religious routine, and it has not developed as scientifically theoretic. Amid the limitations of the study of khitobah as part of Islamic rhetoric, this paper will elaborate on the dynamics and span developments periods.